Cryptosporidium surrogate removal in five commonly used point-of-use domestic filters. (December 2021) - Pang, Liping; Lin, Susan; Premaratne, Aruni; Tham, Annabelle; Abraham, Phillip; Nokes, Chris
Abstract: Point-of-use filters are the major means of treating household drinking-water from non-reticulated water supplies, especially in developing communities, but their effectiveness at removing protozoa varies greatly. We custom built a full-scale filter test rig to simulate typical household use conditions (40 psi, 21.6 L water/day treated, intermittent operation), and assessed the efficiencies of five commonly used low-cost household filter cartridges at removing glycoprotein-coated 4.5 μm polystyrene microspheres that had been validated as a surrogate for Cryptosporidium oocysts. The filter cartridges included 1 μm nominal activated carbon, 1 μm nominal polypropylene, 1 μm nominal polyester, 1 μm absolute pleated-paper and 2 μm nominal silver-impregnated carbon. The data from 120 test runs (duplicate filters, 24 replicate runs per filter type) indicated that the surrogate particles' log10 reduction values (LRVs) were 3.93–4.54 in the 1 μm activated carbon filters, 1.95–2.94 in the 2 μm silver-impregnated carbon filters, and <1.0 in the 1 μm polypropylene, 1 μm polyester and 1 μm pleated-paper filters. To achieve an LRV >3, which is a requirement of domestic drinking-water treatment units for protozoan reduction, 1 μm activated carbon filters are recommended. To satisfy protozoan removal requirements when using the other four filter types tested, additional treatment, for example, water boiling or ultraviolet disinfection, is necessary. Highlights: 5 commonly used household filters were tested for Cryptosporidium surrogate removal. Surrogate reductions were 3.93–4.54 log in 1 μm carbon block filters. 2 μm silver-impregnated carbon filters showed surrogate reduction 1.95–2.94 log. Reductions were <1 log in 1 μm polypropylene, polyester and pleated-paper filters.